Efficient Synthesis of Several Natural Oligostilbenes from the Biomimetic Oxidation of Brominated Isorhapontigenin - Guan, Xingchao; Liu, Meijie; Shao, Zhibo; Li, Hongpeng; Ran, Lu; Li, Wenling (Synthesis, 2019)
This study extensively investigated the regioselective oxidative coupling reactions of 5-bromoisorhapontigenin catalyzed by FeCl3·6H2O or HRP/H2O2 in different solvent systems and the distinct reductive debromination of the isolated dimeric coupling intermediates. Natural (±)-bisisorhapontigenin A and (±)-lehmbachol A and B were efficiently prepared. (±)-Gnetuhainin I, (±)-gnemontanin E, (±)-7-O-ethylgnetuhainin I, and (±)-gnemontanin F were synthesized for the first time.
Keywords: isorhapontigenin; oligostilbenes; regioselectivity; biomimetic synthesis; oxidative coupling; debromination